2016
DOI: 10.1016/j.yexcr.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Dot1l deficiency leads to increased intercalated cells and upregulation of V-ATPase B1 in mice

Abstract: The collecting duct in the mammalian kidney consists of principal cells (PCs) and intercalated cells (ICs), which regulate electrolyte/fluid and acid/base balance, respectively. The epigenetic regulators of PC and IC differentiation remain obscure. We previously used Aqp2 and V-ATPase B1B2 to label PCs and ICs, respectively. We found that mice with histone H3 K79 methyltransferase Dot1l disrupted in Aqp2-expressing cells (Dot1lAC) vs. Dot1lf/f possessed ~20% more ICs coupled with a similar decrease in PCs. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…Hes1 might repress IC genes in PC cells by enhancing chromatin modification enzymes since the inactivation of histone methyltransferase Dot1l appeared to convert PCs into ICs (Xiao et al, 2016). In sum, Notch signaling might antagonize Tfcp2l1 in PC cells where Notch activates Hes1 .…”
Section: Discussionmentioning
confidence: 99%
“…Hes1 might repress IC genes in PC cells by enhancing chromatin modification enzymes since the inactivation of histone methyltransferase Dot1l appeared to convert PCs into ICs (Xiao et al, 2016). In sum, Notch signaling might antagonize Tfcp2l1 in PC cells where Notch activates Hes1 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, lithium treatment [54] results in increased number of intercalated cells along with a decrease in principal cell number which may be due to principal cell trans-differentiation into intercalated cells. More recently the inactivation of dot1l , a histone H3-K79-methyltransferase, in Aqp2 -expressing cells resulted in increased intercalated cell numbers and reduced principal cells numbers [55]. In other instances such as culturing isolated intercalated cells or during the recovery after cessation of lithium treatment the intercalated cells possibly convert into principal cells [56, 57].…”
Section: Discussionmentioning
confidence: 99%
“…H3K79me2 generally correlates with transcriptional activity 12,14,20,50,[52][53][54][55] . However, repressive functions of DOT1L have been proposed as well [56][57][58][59] . Comparing H3K79me2 ChIP values in WT cells with the gene expression changes caused by loss of DOT1L revealed that the genes upregulated in Dot1L-KO B cells were mostly hypomethylated in WT cells, indicating that they are likely indirectly affected by the loss of DOT1L ( Fig.…”
Section: Dot1l-mediated H3k79 Methylation Is Associated With Gene Actmentioning
confidence: 99%